2007
DOI: 10.1176/appi.ps.58.7.914
|View full text |Cite
|
Sign up to set email alerts
|

The State Policy Context of Implementation Issues for Evidence-Based Practices in Mental Health

Abstract: States are key to implementing evidence-based practices, but state mental health authorities should note that each of the practices requires different skill sets and involves different stakeholders. Thus implementing many evidence-based practices at once may not yield economies of scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 0 publications
5
59
0
Order By: Relevance
“…The as-yet unrequited search for simple indicators that reliably predict the adoption and implementation of innovations (i.e., new products, services, or processes) in general, and of one or more specific innovations, has a long history in organizational research and a shorter one in services research (Simpson 2002;Saldana et al 2007). Recent results of a qualitative study of five evidence-based mental health practices for adults being used in eight states suggest, as well, that the configuration of service system infrastructure (i.e., financing, regulations) and implementation support (i.e., training) differs in accordance with demand characteristics of specific evidence-based practices (Isett et al 2007). The current survey asked directors to consider the importance of the DOOR-R factors to implementation success collectively across the several new treatments and services attempted by their organizations, and thus may have obscured relations between these factors and a specific treatment or service.…”
Section: Discussionmentioning
confidence: 99%
“…The as-yet unrequited search for simple indicators that reliably predict the adoption and implementation of innovations (i.e., new products, services, or processes) in general, and of one or more specific innovations, has a long history in organizational research and a shorter one in services research (Simpson 2002;Saldana et al 2007). Recent results of a qualitative study of five evidence-based mental health practices for adults being used in eight states suggest, as well, that the configuration of service system infrastructure (i.e., financing, regulations) and implementation support (i.e., training) differs in accordance with demand characteristics of specific evidence-based practices (Isett et al 2007). The current survey asked directors to consider the importance of the DOOR-R factors to implementation success collectively across the several new treatments and services attempted by their organizations, and thus may have obscured relations between these factors and a specific treatment or service.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there continues to be keen interest in systematically assessing state-level influences on implementation. A qualitative study of the role of the SMHA in implementing EBP's conducted for the National Implementing Evidence-Based Practices Project by the MacArthur Foundation found that financing and regulations, leadership, and training were important to successful implementation (Isett et al 2007(Isett et al , 2008. McFarlane et al (2001) concluded that a strong positive relationship between the SMHA and the provider community was a key ingredient in the success of statewide implementation of family psychoeducation.…”
Section: Introductionmentioning
confidence: 99%
“…Five EBPs in eight states were studied, providing data on the effectiveness of an EBP implementation model involving state oversight and site level implementation support, and creating a rich qualitative database on the program level barriers, strategies and facilitators of EBP implementation over time (Torrey et al 2005;McHugo et al 2007). The MacArthur Mental Health Policy Research Network used the opportunity created by the National Implementing EBPs Project to examine statelevel EBP activities and innovations (Isett et al 2007(Isett et al , 2008. The scale described in this paper evolved from an interest in linking these two studies to explore the relationship between state conditions and the success of EBP implementation in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Since several of the evidence-based practices require fundamental shifts in treatment philosophies, especially those practices that involve non-traditional services such as Illness Management and Recovery (Isett et al 2007), it is important for SMHAs to engage service providers in open dialog about ideas for change. An open dialog will aid in developing trust among the members of the system so that all viewpoints, both dissenting and agreeing, are heard and valued.…”
Section: Discussionmentioning
confidence: 99%